The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1039/c8gc00514a
|View full text |Cite
|
Sign up to set email alerts
|

Conservative evolution and industrial metabolism in Green Chemistry

Abstract: Chemical substances and processes that play a fundamental role in the 12 principles of Green Chemistry representing conservative evolution and/or industrial metabolism were reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 151 publications
(170 reference statements)
0
21
0
1
Order By: Relevance
“…We demonstrated that LA can be converted to GVL in H-Cube ® reactor under 100 bar of H 2 at 100°C exhibiting productivity (hereafter P (mol GVL g metal –1 h –1 )) of 0.83 for Ru/C and 0.2 for Pd/C in water at 100 bar, respectively [53]. From the viewpoint of green chemistry, the use of water or alcohols as reaction media are much more favourable, since they have been considered as environmentally benign or even renewable-based solvents having low negative impacts on the environment [54].…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that LA can be converted to GVL in H-Cube ® reactor under 100 bar of H 2 at 100°C exhibiting productivity (hereafter P (mol GVL g metal –1 h –1 )) of 0.83 for Ru/C and 0.2 for Pd/C in water at 100 bar, respectively [53]. From the viewpoint of green chemistry, the use of water or alcohols as reaction media are much more favourable, since they have been considered as environmentally benign or even renewable-based solvents having low negative impacts on the environment [54].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, application of these two powerful methods in combination for a C–C bond formation process shorten the synthesis sequence for the assembly of the target molecules and thus enhances the ease of preparation of various functional molecules. These processes are considered as “green” because of atom economy and synthetic brevity [ 52 ] involved in these reactions [ 12 , 53 54 ]. Additionally, several methods are available to remove palladium and ruthenium impurities in minor amounts from the reaction mixture.…”
Section: Discussionmentioning
confidence: 99%
“…As postulated by the second law of thermodynamics, any process only occurs with the degradation (anergy) of a part of useful energy (exergy) and transformation of matter from a low entropy state (high organization) to a high entropy state (low organization, high stability) [5,50]. Thus, the idea of a circular (or closed) economy is inconceivable (although it has permeated GC discussions) [3,[60][61][62][63][64][65][66][67], since the total energy is maintained throughout the process, but the possibility of its use is always diminished [50, 68,69]. Besides the physical limits imposed on technologies, which inexorably lead to environmental degradation, there are also problems of technological efficiency, i.e., it is not always that theoretical yields are attained in practice [53].…”
Section: Green Chemistry: Environment Economy and Society?mentioning
confidence: 99%